The transformation of the Conception of Security in NATO and the EU : The Cases of Bosnia and Kosovo - Davutlu, Ferhan (My University, 2019)
Soğuk Savaş‟tan sonra, güvenlik tanımı ve tehdit algısı değişmiştir.Güvenlik çok boyutlu ve çok katmanlı olarak incelenmeye başlanmıştır.Güvenlik alanındaki bu dönüşüm ve değişim uluslararası örgütleri deetkilemiştir. Özellikle AB ve NATO yeni ortaya çıkan tehditler ve güvenlikortamında güvenlik konseptlerini dönüştürmeye başlamışlardır. AB güvenlikkaygısı temelinde kurulmuş bir örgüt olsa da , ekonomik ve politik alandagelişmeye ve derinleşmeye başlamıştır. Kuruluşunun ilk yıllarında ABgüvenlik alanında yeterince başarı sağlayamadı, ancak özellikle MaastrichtAntlaşması'ndan sonra AB güvenlik alanında büyük değişiklikler vedönüşümler göstermeye başladı.Günümüzde, AB kendine özgü bir güvenlikkurumsallaşması göstermektedir. Diğer bir uluslararası örgüt olan NATO,üyelerine kollektif savunma sağlama amacı ile kurulmuş bir uluslararasıgüvenlik örgütüdür. Yeni güvenlik ortamının yarattığı tehditlere karşı güvenlikkonseptini geliştirmeye ve dönüştürmeye başlamıştır. Kollektif güvenliktemelinde başlayan dönüşüm, günümüzde Kooperatif güvenlik konseptitemelinde devam etmektedir. Ancak, NATO yeni güvenlik ortamının yarattığıtehditlere karşı kollektif güvenlik ve kooperatif güvenlik konseptleri temelindedönüşümünü sürdürmüş olsa da, NATO'nun hala kollektif savunma konseptiniön plana alan güvenlik örgütü olduğu görülmektedir. Bu çalışma ile Soğuk Savaş sonrası dönemde AB ve NATO'nungüvenlik dönüşümleri Bosna ve Kosova Savaşları incelenerek anlatılmayaçalışılmıştır.

The meaning of security and the threat perceptions have changed since the Cold War. Security has started to be examined as multi-dimensional and multi-layered. This transformation and change in the field of security has also affected international organizations. In particular, the EU and NATO have begun to transform security concepts in emerging threats and the security environment. Although the EU is an organization established on the basis of security concerns, it has started to develop and deepen in the economic andpolitical sphere. In the first years of establishment, the EU failed to provide enough success in the field of security, but especially after the Maastricht Treaty, the EU began to show great changes and transformations in the field of security. Today, it can be said that the EU has evolved into a sui generis security institutionalization. NATO, another international organization, is aninternational security organization established to provide collective defense to its members. It has started to develop and transform the security concept against the threats posed by the new security environment. The transformation started on the basis of collective security and continues on the basis of the concept of cooperative security. However, although NATO has begun to transform against the threats posed by the new security environment on the basis of collective security and cooperative security concepts, NATO still appears to be a security organization that prioritizes the concept of collective defense. In this study, I tried to define the transformation in the security conceptions of NATO and the EU after the Cold War through an analysis of their stance on the conflicts in Bosnia and Kosovo.
Keywords: Avrupa Birliği; European Union; Güvenlik; NATO; NATO Security; Political science; Siyasal bilim